Subsídios para o manejo de Cedrela fissilis (Vell.) em floresta estacional decidual secundária - Pereira, Lilian Daniel (2015)
The forest management of native species has shown great potential for the production of timber. Therefore, the study of aspect since seedling initial growth until mature tree is essential. Som, this study aimed to evaluate diameter distribution, spatial distribution healthy, height increment, diameter increment and volume of cedar individuals. Young and adults individuals have been measured in their height, diameter of the base or DBH, the competition around these by measure of point density, basal area of Bitterlich and vertical competition index. All cedars higher than 15 cm had their coordinates obtained with GPS and had noted their characteristics and health state as present pest attack damage for spatial distribution. The increment of adult trees was obtained by Presler trade and some trees were slaughtered for stem analysis (ANATRO). Frequency histogram diameter, analysis of special distribution by function K of Ripley, stepwise regression analysis for diameter increment and height increment in function of measure variable were made. The diametrical distribution had negative exponential form for both young and adult individuals. The young trees were clustered, while adult trees were random. The equacion for height increment included initial height and basal area. A model for diameter increment of young tree was not possible to make due to their high variation. The young trees were attacked by the moth and the sawyer. The intensity of moth attack was higher in areas with low total density of trees, and sawyer attack was higher in areas with high density of plant with attack dimensions cedar (between 8 and 12 cm of diameter of base). The model of diameter increment of adult trees included crown class, initial diameter. The model of transversal area increment included hypsometric relationship, crown class and range index. The diameter increment was clearly lower in the oppressed trees than in the tree of emergent stratum. The best model for describing volume was Ogaya. From de above results it was concluded that the cedar is a gap-phase species. Are required few matrices trees per hectare for ensure its regeneration, the growth of young trees is benefited by presence of taperas bracken and for areas with lower basal area, however, very open areas provide the moth attack. For the management of cedar in native forests should be prioritized trees with lower hypsometric relations and greater range index, and should keep cedar in areas with basal area lower than 30m², because basal area greater than this value becomes very high competition for the species.